Unconfined Compressive Strength of Aqueous Polymer-Modified Saline Soil - Yan Zhu; Xiangjuan Yu; Lei Gao; Jiajia Chen; Michael Dino Cotugno (International Journal of Polymer Science)
Saline soil is a special soil that consists of fine particles and has poor engineering properties. It causes salt heaving and is collapsible and corrosive. The treatment of this type of soil for the use as a resource for roadbed fillings has been one of the most important engineering topics in highway construction near coastal areas. This study introduces a new type of aqueous polymer, called ZM, which is used to amend and stabilize saline soil. To test the effects of ZM-solidified saline soil, unconfined compressive strength (UCS) tests were carried out on unmodified and ZM-modified saline soil specimens, respectively. The test results show that the ZM additive significantly improves the UCS. Based on the increase of the ZM admixture, the UCS increases with the curing time. The main increment of the UCS occurs within the first seven days of curing. In addition, the salt content has a great influence on the UCS. With increasing ZM concentration and curing time, the water stability and wetting-drying cycling resistance improve. Based on the X-ray diffraction results, the diffraction peaks of ZM-modified saline soil insignificantly change compared with those of unmodified saline soil. However, the SEM images indicate the formation of membrane structures in ZM-modified saline soil. The modification process produces denser and more stable soil because the reaction products fill voids inside the soil and form a viscous membrane structure on the soil surface.